2009
DOI: 10.1002/asmb.758
|View full text |Cite
|
Sign up to set email alerts
|

Markovian analysis for automatic new topic identification in search engine transaction logs

Abstract: Topic analysis of search engine user queries is an important task, since successful exploitation of the topic of queries can result in the design of new information retrieval algorithms for more efficient search engines. Identification of topic changes within a user search session is a key issue in analysis of search engine user queries. This study presents an application of Markov chains in the area of search engine research to automatically identify topic changes in a user session by using statistical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…The large majority of the studies on query modification used search logs of search engines for textual content. Probably the most studied search logs are those of the Excite search engine (Bozzon et al, 2007; Lau & Horvitz, 1999; Özmutlu, 2009; Rieh & Xie, 2006; Whittle et al, 2007). Other studies analyzed logs of Dogpile (Jansen et al, 2009), Tumba (Costa & Seco, 2008), AOL (Huang & Efthimiadis, 2009), Fast (Özmutlu, 2009), and Yahoo!…”
Section: Related Workmentioning
confidence: 99%
“…The large majority of the studies on query modification used search logs of search engines for textual content. Probably the most studied search logs are those of the Excite search engine (Bozzon et al, 2007; Lau & Horvitz, 1999; Özmutlu, 2009; Rieh & Xie, 2006; Whittle et al, 2007). Other studies analyzed logs of Dogpile (Jansen et al, 2009), Tumba (Costa & Seco, 2008), AOL (Huang & Efthimiadis, 2009), Fast (Özmutlu, 2009), and Yahoo!…”
Section: Related Workmentioning
confidence: 99%
“…Hence, DempsterShafer was tested under five different configurations detailed in [50,53]. According to Özmutlu and Çavdur [50] the parameters obtained for one particular dataset are not necessarily the most successful ones to segment that dataset and the results obtained by this author confirm this claim.…”
Section: Resultsmentioning
confidence: 70%
“…Since then, they and their colleagues have revisited the Dempster-Shafer method [53] and studied the feasibility of additional ones: neural networks [51,52], multiple linear regression [48,55], Monte-Carlo simulation [49] and conditional probabilities [54].…”
Section: Machine-learning Methods To Combine Temporal and Lexical Cluesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the runs with T D 7 factors, we simply omitted the estimated topics with the smallest estimated probabilities from Equation (2) in the calculations in Equations (3)- (6). We used an enumerative search to identify the best match between estimated and true topics in Equations (3) and (4). In our analysis, we found that all results for the KL divergence responses (3) and (5) are the same as for the RMS distance responses (4) and (6).…”
Section: Numerical Studymentioning
confidence: 90%